FRI0379 Prevalence of FAM111 B gene mutations in systemic sclerosis. (15th June 2017) - Gcelu, A; Deshpande, G; Kalla, AA; Tikly, M; Mayosi, B; Hodkinson, B
Abstract : Background: Systemic sclerosis (SSc) is a prototypic systemic fibrotic disease with unclearly characterized genetic basis. Implicated genes have been associated with autoimmune dysregulation with relatively few variants associated with fibrosis [1]. We have discovered that mutations in FAM111B gene cause hereditary fibrosing poikiloderma with tendon contractures, myopathy, and pulmonary fibrosis (POIKTMP)[2], a multisystem fibrotic condition with clinical aspects of SSc [3]. This observation has established FAM111B as a candidate gene for SSc. Objectives: The objective is to investigate whether FAM111B gene mutations are present in SSc patients and further explore relationships between FAM111B mutations and clinical expression of SSc. Methods: Patients with a definite diagnosis of SSc attending the Rheumatology outpatient departments at Groote Schuur Hospital, Cape Town, and Chris Hani Baragwanath Hospital, Johannesburg, were enrolled into the study. Physical examination assessing the extent of disease was done in all patients and the modified Rodnan skin score (mRSS) was used to determine the extent of the skin involvement. Blood samples were collected for DNA extraction and mutation screening using the high-resolution melt technique. Samples with abnormal electropherograms were selected for Sanger sequencing to identify mutations. Public databases were used to verify the frequency of variants in FAM111B . Results: 131 patients were genotyped, 13 men and 118 women, with a mean age of 26.6 years and mean age of symptom onset at 25.3 years. The majority of patients were black (59.5%). 72% of patients had diffuse systemic sclerosis (DSSc) with a median mRSS of 11. Genetic analysis revealed seven rare genetic variants (C832G>A; C855G>T; C917A>G; C937G>A; C988C>T; C995A>C and C1006G>C) in eight patients (five patients from Johannesburg and three patients from Cape Town) [table 1]. These variants were missense mutations of unknown significance with a minor allele frequency <0.01. No FAM111B mutations that cause POIKMT were found in patients with SSc. Conclusions: Rare genetic variants of unknown significance (GVUS) in FAM111B gene were found in patients with SSc. It is possible that the GVUS may modify the function of FAM111B, and influence the pathogenesis of SSc or are rare polymorphisms with no functional impact. References: Romano, E., et al., The genetics of systemic sclerosis: an update. Clin Exp Rheumatol, 2011. 29(2 Suppl 65): p. S75–86. Mercier, S., et al., Mutations in FAM111B cause hereditary fibrosing poikiloderma with tendon contracture, myopathy, and pulmonary fibrosis. Am J Hum Genet, 2013. 93(6): p. 1100–7. Khumalo, N.P., et al., Poikiloderma, tendon contracture and pulmonary fibrosis: a new autosomal dominant syndrome? Br J Dermatol, 2006. 155(5): p. 1057–61. Disclosure of Interest: None declared